IMPLIKASI DAMPAK KARAKTERISTIK PERUSAHAAN DAN CORPORATE GOVERNANCE TERHADAP PENGUNGKAPAN SUSTAINABILITY REPORTING - Maria Yuliana Samosir (2017)
The purpose of this study is to examine the impact of companies characteristic and corporate governance for sustainability reporting disclosure. Total population of this research are 38 companies that makes Sustainability Reporting and listed on Indonesia Stock Exchange in 2012 to 2015. Sample of this research selected by purposive sampling method thus obtained 13 companies with 4 years observation period. The analysis technique used in this research is multiple linear regression and hypothesis testing using classic assumption test, the t-statistic and the F-statistic with a significance level of 5%. The result of this study indicate that Adjusted R Square of 0,148 or 9,6%, which means the ability of independent variables are liquidity, leverage, activity, and board of commissioner by 14,8% in explaining the dependent variable is sustainability reporting disclosure. Simultaneously liquidity, leverage, activity and board of commissioner has significant effect on sustainability reporting disclosure. Liquidity has a significant influence on Sustainability Reporting. Leverage, activity, and board of commissioner has not significant effect on Sustainability Reporting.